Microbial Communities Associated With Passive Acidic Abandoned Coal Mine Remediation - Ly, Truc; Wright, Justin R.; Weit, Nicholas; McLimans, Christopher J.; Ulrich, Nikea; Tokarev, Vasily; Valkanas, Michelle M.; Trun, Nancy; Rummel, Shawn; Grant, Christopher J.; Lamendella, Regina (Frontiers in Microbiology, 2019)
Acid mine drainage (AMD) is an environmental issue that can be characterized by either acidic or circumneutral pH and high dissolved metal content in contaminated waters. It is estimated to affect roughly 3000 miles of waterways within the state of Pennsylvania, with half being acidic and half being circumneutral. To negate the harmful effects of AMD, ~300 passive remediation systems have been constructed within the state of Pennsylvania. In this study, we evaluated the microbial community structure and functional capability associated with Middle Branch passive remediation system in central PA. Sediment and water samples were collected from each area within the passive remediation system and its receiving stream. Environmental parameters associated with the remediation system were found to explain a significant amount of variation in microbial community structure. This study revealed shifts in microbial community structure from acidophilic bacteria in raw AMD discharge to a more metabolically diverse set of taxa (i.e. Acidimicrobiales, Rhizobiales, Chthoniobacteraceae) towards the end of the system. Vertical flow ponds and the aerobic wetland showed strong metabolic capability for sulfur redox environments. These findings are integral to the understanding of designing effective passive remediation systems because it provides insight as to how certain bacteria (SRBs and SOBs) are potentially contributing to a microbially mediated AMD remediation process. This study further supports previous investigations that demonstrated the effectiveness of sulfate reducing bacteria (SRBs) in the process of removing sulfate and heavy metals from contaminated water.